PELAKSANAAN IHDAD PADA MASA IDDAH BAGI JANDA BURUH PABRIK : KONFLIK ANTARA KEWAJIBAN HUKUM DAN TUNTUTAN EKONOMI (STUDI KASUS DESA LUBANG BUAYA KEC. SETU KAB. BEKASI) - Ahmad Harisul Miftah; Muhammad Azqia Ali (Syaksia: Jurnal Hukum Perdata Islam, 2026)
The implementation of ihdad during the iddah period is a shar‘i obligation for women whose husbands have passed away. However, in the context of modern society, particularly for women working as factory laborers, this obligation often conflicts with urgent economic demands. This study aims to analyze the practice of ihdad during the iddah period among widowed factory workers in Lubang Buaya Village, Setu District, Bekasi Regency, and to examine the conflict between Islamic legal obligations and economic necessities they face. This research employs an empirical legal research method with a qualitative approach. Data were collected through in-depth interviews, observation, and documentation involving widowed factory workers, village officials, and community leaders. The findings indicate that most widowed factory workers continue to work during the iddah period due to economic constraints and the absence of alternative sources of livelihood. Nevertheless, they attempt to adjust the practice of ihdad by maintaining modest behavior and avoiding excessive adornment. From the perspective of Islamic law, this practice can be understood through the framework of maqāṣid al-sharī‘ah and the principle of necessity (al-ḍarūrāt tubīḥ al-maḥẓūrāt), which emphasize public welfare and the protection of livelihood. This study concludes that the implementation of ihdad for widowed factory workers should be interpreted contextually so that Islamic law remains relevant, just, and responsive to the socio-economic realities of working women.